Determination of human DNA replication origin position and efficiency reveals principles of initiation zone organisation. Issue 13 (8th July 2022) - Guilbaud, Guillaume; Murat, Pierre; Wilkes, Helen S; Lerner, Leticia Koch; Sale, Julian E; Krude, Torsten
Abstract: Replication of the human genome initiates within broad zones of ∼150 kb. The extent to which firing of individual DNA replication origins within initiation zones is spatially stochastic or localised at defined sites remains a matter of debate. A thorough characterisation of the dynamic activation of origins within initiation zones is hampered by the lack of a high-resolution map of both their position and efficiency. To address this shortcoming, we describe a modification of initiation site sequencing (ini-seq), based on density substitution. Newly replicated DNA is rendered 'heavy-light' (HL) by incorporation of BrdUTP while unreplicated DNA remains 'light-light' (LL). Replicated HL-DNA is separated from unreplicated LL-DNA by equilibrium density gradient centrifugation, then both fractions are subjected to massive parallel sequencing. This allows precise mapping of 23, 905 replication origins simultaneously with an assignment of a replication initiation efficiency score to each. We show that origin firing within early initiation zones is not randomly distributed. Rather, origins are arranged hierarchically with a set of very highly efficient origins marking zone boundaries. We propose that these origins explain much of the early firing activity arising within initiation zones, helping to unify the concept of replication initiation zones with the identification of discrete replication origin sites.